On the Irreversible Thermodynamic Framework for Closed Systems Consisting of Chemically Reactive Components - A. Bhalekar, Anil (Asian Journal of Chemistry, 2010)
A methodology has been described to develop an irreversible thermodynamic framework based on the laws of thermodynamics and exemplified by applying it to a spatially uniform chemically reacting closed system with no irreversibility in the energy exchanges. It is shown that if in the Gibbs reration the chemical composition determining extensive parameters appear as independent thermodynamic variables and if their variation includes the changes due to chemical reaction, then it, in fact, is an irreversible thermodynamic description. The de Donderian thermodynamic framework is basically a nonequilibrium description in which the chemical affinity containing term is the manifestation of the irreversibility in chemical interactions. This confirms that the Gibbs function primarily takes care of the chemical interactions and hence the quantification of the irreversibility in the latter need to be achieved through the former function by identifying its suitable expression.